Spontaneous Rupture of Adrenal Myelolipoma: A Case Report With Review of the Literature - Yasushi Mochizuki; Kyohei Araki; Kensuke Mitsunari; Takahisa Iwata; Tomohiro Matsuo; Tomoaki Hakariya; Kojiro Ohba; Ryoichi Imamura (IJU Case Reports)
ABSTRACT Introduction Adrenal myelolipoma is often asymptomatic and is commonly diagnosed using imaging modalities. Herein, we report a case of adrenal myelolipoma detected through spontaneous rupture and review similar cases from the literature. Case Presentation A 27‐year‐old man was admitted to our hospital with sudden right flank pain. Abdominal computed tomography revealed right retroperitoneal hemorrhage due to a spontaneous rupture of a retroperitoneal tumor. He underwent emergency transcatheter arterial embolization because of his severe symptoms and poor general condition, which included abdominal pain and progressive anemia. We performed laparoscopic resection of the tumor with the right adrenal gland 3 months after the emergency embolization. Consequently, a definitive diagnosis of adrenal myelolipoma was confirmed. Conclusion Adrenal myelolipoma, although scarcely reported, can rupture spontaneously and lead to severe consequences. Treatment options may include percutaneous arterial embolization and subsequent surgery.